GENETICS OF DEMENTIA: THE CANDIDATE GENES AND AVAILABLE GENETIC TESTINGS - Ziske Maritska; Diah Andini; Febryana Ramadhani Machyar; Rachmat Taufan; Try Merdeka Puri; Tryvanie R Putra; Uswati Uswati; Bintang Arroyantri Prananjaya; Rini Nindela; Nita Parisa (Indonesian Journal for Health Sciences, 2023)
When dementia is present, a person's memory, reasoning, behavior, and even their capacity to carry out day-to-day chores can all become distorted. This syndrome remains present and actually worsens as time passes. It's possible that synapse loss, death and dysfunction of brain cells, gliosis, and inflammation are all factors in the progression of dementia. The clinical syndrome, age, and a history of the ailment in the patient's family should dictate the choices made about counseling and testing. Dementia is known as a multifactorial condition, brought on by the combination of strong genetic factors and environmental factors. There are several candidate genes  associated with Dementia; APP, PSEN1, and PSEN2 genes, in addition to the GRN and MAPT genes. This literatura review provide insight on the genetic of Dementia, particularly in the genetic causes and testings